METODOLOGÍA PARA AMPLIAR LA CARTOGRAFÍA CORINE MEDIANTE EL ANÁLISIS O.B.I.A. DE IMÁGENES LANDSAT - Ramos, Victoriano (2016)
The European Union program Corine Land Cover has brought a revolution in the analysis of territorial dynamics, to provide data on land use and its changes from 1991 to 2006. It is a reliable and effective reference for the analysis and regional planning. However, a period of 15 years may be ineffective if it is intended to contextualize territorial dynamics of higher temporal amplitude. In this study we propose a method to extend the Corine mapping by analyzing satellite images obtained over the 40 years of Landsat mission. For this, we have used the latest available algorithms for identifying objects in images (Objet-Based Image Analysis: O.B.I.A.). To check the reliability of this methodology, we used the region of Vegas Altas del Guadiana as study area. The territorial dynamism continued over time around irrigated agriculture and the spatial and spectral characteristics of these uses make this region an ideal area to develop this study.